2012
DOI: 10.1007/s00784-012-0777-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of high mobility group box protein 1 and intermittent PTH (1–34) in periodontal tissue repair following orthodontic tooth movement in rats

Abstract: The findings point to the potential benefit of iPTH in the attempt to support these immune-associated reparative processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In vitro and in vivo studies have shown that HMGB1 may be essential to the differentiation of osteoclast precursors by RANKL [35]. Also, HMGB1 was shown to be associated with RANKL in the regulation of host response during periodontal repair following orthodontic tooth movement in rats [36]. More studies are necessary to investigate the role of HMGB1 in osteoclastogenesis during periodontal disease to better elucidate whether this protein has important participation, whether alone or in cooperation with other osteoclastogenesis-inducing signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that HMGB1 may be essential to the differentiation of osteoclast precursors by RANKL [35]. Also, HMGB1 was shown to be associated with RANKL in the regulation of host response during periodontal repair following orthodontic tooth movement in rats [36]. More studies are necessary to investigate the role of HMGB1 in osteoclastogenesis during periodontal disease to better elucidate whether this protein has important participation, whether alone or in cooperation with other osteoclastogenesis-inducing signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze glycine receptor expression, tissue sections were processed for immunohistochemical detection of glycine receptor expression according to previously established protocols [22, 23]. In brief, sections were incubated with primary antibody of rabbit origin raised against a peptide mapping at the carboxy terminus of the protein (anti-glycine receptor, SYSY, Göttingen, Germany) in a 1 : 250 working solution of TBS/BSA at 4°C overnight in a humidified chamber.…”
Section: Methodsmentioning
confidence: 99%
“…HMGB1 induces human lung endothelial cell cytoskeletal rearrangement and barrier disruption (Wolfson et al, 2011). In addition, HMGB1 promotes periodontal remodeling and repair (Wolf et al, 2012; Wolf et al, 2013a; Wolf et al, 2013b; Wolf et al, 2013c). …”
Section: Hmgb1 Functionmentioning
confidence: 99%